Large screening of DNA-compatible reaction conditions for Suzuki and Sonogashira cross-coupling reactions and for reverse amide bond formation. (1st July 2021) - Favalli, Nicholas; Bassi, Gabriele; Bianchi, Davide; Scheuermann, Jörg; Neri, Dario
Graphical abstract: Abstract: Progress in DNA-encoded chemical library synthesis and screening crucially relies on the availability of DNA-compatible reactions, which proceed with high yields and excellent purity for a large number of possible building blocks. In the past, experimental conditions have been presented for the execution of Suzuki and Sonogashira cross-coupling reactions on-DNA. In this article, our aim was to optimize Suzuki and Sonogashira reactions, comparing our results to previously published procedures. We have tested the performance of improved conditions using 606 building blocks (including boronic acids, pinacol boranes and terminal alkynes), achieving >70% conversion for 84% of the tested molecules. Moreover, we describe efficient experimental conditions for the on-DNA synthesis of amide bonds, starting from DNA derivatives carrying a carboxylic acid moiety and 300 primary, secondary and aromatic amines, as amide bonds are frequently found in DNA-encoded chemical libraries thanks to their excellent DNA compatibility.